From the age of migration to the century of security: the emergence of ‘control policy with a (in)human face’ - Ramírez, Jaques (FLACSO - Sede Ecuador, 2018)
Although the official discourse, accepted practically by all the States, speaks of a "regular, orderly and safe" migration, which has been sealed in the Global Compact for Migration, contemporary human mobility differs greatly from the desire of the rulers both in the profile and in the routes used to reach destination. This article reviews a number of 'migratory landscapes' in several places on the planet that have had as a correlate the State´s response to greater controls, appealing to the discourse of national sovereignty. The following thesis is proposed: that in this new stage of neoliberalism we are witnessing the emergence of control policy with an (in) human face of neo-fascist character, especially with the rise to power of nationalist and far-right governments that promote and practice xenophobia, racism and aporophobia. This has resulted in increased deportation, judicialization of migration, expulsion, confinement, construction of walls, extortion, kidnapping, disappearances, torture and death.